Geographies for a good birth: a geo(corpo)graphic approach to home birth in Chile - Pía Rodríguez-Garrrido (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2022)
Home birth has added a layer of complexity to the epistemology of birth, raising questions about its institutional aspects. From this standpoint, this article stems from an interest in the narratives that Chilean women ascribe to the scenario of home birth. Thirty women were interviewed between October 2018 and January 2019 using elements of body mapping. A central category emerged in thematic analysis: geo(corpo)graphies of home birth, which involves the deployment of the material/symbolic body in a manner that allows birth to occur. Three subcategories also emerged: creating the ideal setting for childbirth, which has to do with imagining and defining the ideal space for childbirth; the best place to give birth letting instincts flow, which is constructed by feeling and listening to the body; and resignifying the ideal scenario, which implies attributing a new meaning to the home in order to give birth. These geo(corpo)graphic narratives of home birth recognize corporality and its disposition in space, allowing birth to be collectively socialized, blurring the boundaries between the public and the private.